2015
DOI: 10.1002/ejlt.201500018
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of plant materials in “Serra da Estrela” cheese improves antioxidant activity without changing the fatty acid profile and visual appearance

Abstract: ‘Serra da Estrela’ cheese is a Portuguese delicacy, which has been produced for centuries from the milk of cattle pasturing in the protected Serra da Estrela natural park. Transforming this cheese into a functional food would be a huge benefit for the market and the consumer. Decocted extracts, dried chestnut flowers and lemon balm plants were incorporated into the cheese to functionalise it, granting antioxidant activity to this foodstuff. The functionalised cheeses showed higher antioxidant activity, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…Carocho et al . () investigated the effects of the application of dried chestnut ( Castanea sativa Mill.) flowers and its decoction extracts and lemon balm ( Melissa officinalis , L.) and its decoction extracts on the properties of Serra da Estrela cheese.…”
Section: Polyphenols: Synthesis Classification and Consequences In Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Carocho et al . () investigated the effects of the application of dried chestnut ( Castanea sativa Mill.) flowers and its decoction extracts and lemon balm ( Melissa officinalis , L.) and its decoction extracts on the properties of Serra da Estrela cheese.…”
Section: Polyphenols: Synthesis Classification and Consequences In Vmentioning
confidence: 99%
“…Even though 6% hazelnut supplementation exhibited the highest functional properties, the lowest consumer preference was observed compared with yoghurts with 3% San Giovanni and Tonda Gentile Trilobata HS, which received the highest consumer scores. Carocho et al (2015) investigated the effects of the application of dried chestnut (Castanea sativa Mill.) flowers and its decoction extracts and lemon balm (Melissa officinalis, L.) and its decoction extracts on the properties of Serra da Estrela cheese.…”
Section: Effects On Sensory and Physicochemical Properties In Dairymentioning
confidence: 99%
“…Concomitantly, people are progressively receptive to food products prepared with natural ingredients in substitution to general synthetic compounds, which are often associated with unwanted effects (Carocho et al, 2014). In addition to the potential health effects conveyed by the functionalizing agents, the rheological and technological properties of food products themselves might also be improved (Berdahl, Nahas, & Barren, 2010;Caleja et al, 2015;Carocho et al, 2015b; Sciarini, Ribotta, Le on, & P erez, 2012).…”
Section: Characterization Of Different Types Of Functionalized Breadmentioning
confidence: 99%
“…Previous studies from our research group reported the incorporation of other plant species in this cheese, namely chestnut flowers (Castanea sativa Mill.) and lemon balm (Melissa officinalis L.), to promote the shelf life, confer functional properties and maintain sensory features, with very promising conclusions (Carocho, Barreira, et al, 2015). In the present study, and due to its important bioactivities, basil was tested for its functional and preserving properties, in order to develop a novel food product with this natural and appreciated ingredient.…”
Section: Introductionmentioning
confidence: 99%